2008
DOI: 10.1111/j.1349-7006.2008.00987.x
|View full text |Cite
|
Sign up to set email alerts
|

Oxysterol binding protein‐related protein‐5 is related to invasion and poor prognosis in pancreatic cancer

Abstract: In previous studies, the gene expression profiles of two hamster pancreatic cancer cells with different potentials for invasion and metastasis were analyzed. In the present study, we identified that one of the genes expressed strongly in the highly metastatic cell line is hamster oxysterol binding protein-related protein (ORP)-5. The aim of the present study was to clarify the relationship between ORP5 and invasion and poor prognosis of human pancreatic cancer. Invasion assays were carried out in both hamster … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
31
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 41 publications
(33 citation statements)
references
References 43 publications
1
31
0
Order By: Relevance
“…These results suggested that OSBPL5, a metabolism-related molecule, might be involved in metastasis. Consistent with this notion, it was reported earlier that OSBPL5 expression is related to invasion and poor prognosis of pancreatic cancer (29,30). Thus, OSBPL5 may play a role in facilitating metastasis of lung cancer, similar to that suggested for pancreas cancer.…”
Section: Discussionsupporting
confidence: 83%
“…These results suggested that OSBPL5, a metabolism-related molecule, might be involved in metastasis. Consistent with this notion, it was reported earlier that OSBPL5 expression is related to invasion and poor prognosis of pancreatic cancer (29,30). Thus, OSBPL5 may play a role in facilitating metastasis of lung cancer, similar to that suggested for pancreas cancer.…”
Section: Discussionsupporting
confidence: 83%
“…Two kinds of RNA are detectable: mRNA, which codes for proteins, and microRNA, which influences gene expression. Table 1 shows a selected sample of both single and multiple fecal RNA markers [57,74,75,76,77,78]. With different markers and different isolation methods among these studies, the results suggest wide variation in sensitivity, but consistently high specificity.…”
Section: Fecal Rna Markersmentioning
confidence: 97%
“…For instance, mutations in NPC1 and NPC2 are causative for the neurodegenerative Niemann–Pick disease, where cholesterol fails to reach the ER and accumulates in late endosomes (Mukherjee & Maxfield, ). Further, expression of ORP5 has been found to correlate with invasion and poor prognosis of pancreatic cancer (Koga et al , ), and expression of human ORP1L in macrophages enhances atherosclerotic lesion development in LDL receptor‐deficient mice (Yan et al , ). Overexpression of STARD3 induces liver damage in mice (Tichauer et al , ), and increased expression of this protein in human tumours is associated with high‐grade prostate cancer and HER2‐positive breast cancer (Vinatzer et al , ; Stigliano et al , ).…”
Section: Components Of Er–endosome Contact Sites Are Affected In Disementioning
confidence: 99%